Kurikulum Berbasis Kompetensi Kerangka Kualifikasi Nasional Indonesia (KBK-KKNI) (Model Rekonstruksi Madin) - Abdurrahman Abdurrahman (Ta'allum: Jurnal Pendidikan Islam, 2014)
Attempts to match the profiles of graduate with the level of competence in accordance to KKNI (Kerangka Kualifikasi Nasional Indonesia/ Indonesian Qualification Framework) which is issued in 2012, raised a question how about  the competence of graduate from Madrasah Diniyah (Religious School).  With its large quantity, the position of  Madrasah Diniyah (Madin) is still on the sideline. This is due to its conventional approach and exclusiveness. Therefore, developing the potential of Madin institutionally through curriculum reconstruction is urgently needed. The writer found that the KBK KKNI can be the right instrument for this purpose, because the tracer study results are based on the profile of the profession which will directly give impact on institutional development.